ANALISIS PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK PELAKU TINDAK PIDANA KEKERASAN - Zainab Ompu Jainah; Intan Nurina Seftiniara; Sheila Monica Yohanes (Gapenas Publisher, 2021)
Violence can be perpetrated by anyone, both adults and children. Children who are in conflict with the law are usually affected by bad things, both from internal factors and external factors. Children who are experiencing a period of growth will certainly experience identity crisis,where he does not know who he is. This causes children to become more irritable and arise a desire to commit violence. This article is intended to find out how criminal accountability and the factors that cause children to commit violent crimes. Violence is an expression or action that a person or more has done to cause pain or suffering towards another person. The methods used in this study are normative legal research and empirical law, namely research whose sources come from books, legislation, journals, interviews, and other sources which are then analyzed using qualitative analysis methods. In providing criminal liability to children, it is worth diversion first so that children do not feel burdened by the law. In addition, the role of parents is also needed to supervise children in the use of social media so as not to imitate bad things.